Safety voice concept clean-up: examining the voice that challenges us to be safer - Paul, Jeanne; Pilbeam, Colin; Smallwood, Anna (Elsevier, 2025)
Safety voice, the act of speaking up about safety concerns, is essential for preventing accidents and fostering an engaged safety culture. This study systematically reviewed 86 empirical studies of safety voice by operationalising and applying Podsakoff et al.’s (2016) four-stage framework for developing good conceptual definitions to assess its conceptual clarity, triggers, contextual variations, and measurement. This identified opportunities to refine definitions, theory, and hazard categorisation to enable proactive risk management. Current research on communication scope, directionality, and dyadic sender-receiver dynamics is fragmented which limits potential insights. Contextual disparities and Western culture biases affect generalisability. While senior leadership is key to a positive safety culture this focus is lacking. Addressing these areas through improved conceptual frameworks, hazard-voice models, and cross-industry comparisons will enhance proactive safety management, engagement, and resilience in high-risk industries.
Keywords: Human Factors; 40 Engineering; 42 Health sciences; 52 Psychology